Association between the ACE I/D polymorphism and risk of ischemic stroke: An updated meta-analysis of 47,026 subjects from 105 case–control studies - Zhao, Jiangyang; Qin, Xue; Li, Shan; Zeng, Zhiyu (Journal of the neurological sciences, 2014)
The association between the angiotensin-converting enzyme insertion/deletion (ACE I/D) polymorphism and risk of ischemic stroke (IS) remains controversial and ambiguous. To clarify this association, a large meta-analysis was performed. Electronic databases in both English and Chinese were used to identify relevant studies (updated in February 2014). Odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to describe the strength of the association. One hundred and fifty eligible studies, including 18,258 IS cases and 28,768 controls, were identified. Meta-analysis of these studies pointed to a significant association between the ACE I/D polymorphism and IS risk: (D vs. I: OR=1.354, 95% CI=1.272–1.440, P<0.001; DD vs. II: OR=1.755, 95% CI=1.561–1.973, P<0.001; ID vs. II: OR=1.178, 95% CI=1.098–1.263, P<0.001; DD vs. ID/II: OR=1.535, 95% CI=1.399–1.684, P<0.001; DD/ID vs. II: OR=1.353, 95% CI=1.251–1.463, P<0.001). Subgroup analysis revealed a significantly elevated risk among Asians, but with borderline statistical significance among Caucasians. This meta-analysis indicated that the ACE I/D polymorphism may be a genetic susceptibility factor for IS, especially among Asians, but with borderline statistical significance for Caucasians. Further investigations are needed to validate our conclusions. •We report the current totality of evidence on ACE I/D polymorphism and IS risk.•ACE I/D polymorphism is confirmed as a risk factor for IS.•This study may enrich studies on the identification of genetic variations of IS risk.•This study may aid to find the theory for risk prediction, prevention, and therapy.